TimBa Nook / Nur Sabrina Iwani Mohd Yasin, Nurul Husna Abd Rahim and Atikah Fukaihah Amir - Mohd Yasin, Nur Sabrina Iwani; Abd Rahim, Nurul Husna; Amir, Atikah Fukaihah (2024)
TimBa Nook is a blend of timber and bamboo, referring to a small, cozy, and secluded space for reading. The name reflects the space’s cozy and intimate nature, making it an appealing spot within the student hub. The "TimBa Nook" is an innovative student reading area that harmoniously combines timber and bamboo materials to create an eco-friendly, sustainable, and aesthetically pleasing environment. Positioned near a lake, this nook enhances the reading experience by integrating natural elements with functional design. The use of locally sourced timber and bamboo not only supports environmental sustainability but also adds warmth and character to the space. Key features include ergonomic seating, shaded areas, and a community book exchange system. The "TimBa Nook" serves as a model for how natural materials can be used to create both functional and beautiful public spaces.